"Exploring natural coagulants as impending alternatives towards sustainable water clarification" – A comparative studies of natural coagulants with alum. (December 2019) - Saritha, Vara; Karnena, Manoj Kumar; Dwarapureddi, Bhavya Kavitha
Graphical abstract: Highlights: The present study is the first-ever study that has presented DOC induced as a result of treatment with natural coagulants. Functional groups responsible for coagulant activity presented. SEM images presenting adsorbed flocs. Lesser concentrations of coagulants utilized in comparison to the available literature survey. Abstract: The present study is an attempt to address issues of challenges to availability of potable water for moving towards sustainable development. The study tested efficiency of natural coagulants in removing pollutants from surface water. Utilization of natural coagulants come with a drawback of lower shelf life which attributed to induced dissolved organic carbon due to higher concentrations of the coagulants used. Hence, in the present study lower concentrations of the natural coagulants were tested. Further, the efficiency of these coagulants is compared with standard coagulant alum. The efficiency of coagulants on the surface water was dominant in turbidity removal with 78.72% by alum; 69.15% by sago at pH 7 with coagulant dose 0.1 g/L and 0.3 g/L respectively and 67.73% by chitin at pH 6 with coagulant dose 0.3 g/L. FTIR analysis of the coagulants showed amines, hydroxyl, and carboxyl functional groups confirming the polymer forming capability of the coagulants. SEM images of the coagulants before and after treatment showed vibrant proof of interactions between coagulants and suspended solids understood from the changes in the surface morphology. From the results it can be concluded that the natural coagulants tested are promising solutions for challenges of water quality.